Letrozole: an emerging array of hope for infertile women - Maladkar, Manish; Tekchandani, Chitra; Karchodi, Akshata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovulation induction has been a major breakthrough in the management of female infertility since many decades. Letrozole, an aromatase inhibitor has been used as a potential therapy for ovulation induction. A large number of clinical evidences have been emerging which cite the beneficial role of Letrozole in conditions like anovulatory infertility, polycystic ovary syndrome (PCOS), unexplained infertility and an incipient role in endometriosis- related infertility with regards to higher live-birth rates. Letrozole is a superior alternative to Clomiphene citrate (CC) which has been used conventionally as ovulation inducer. Clomiphene citrate has certain well-defined disadvantages, whereas Letrozole overcomes these limitations to a reasonable extent. The peripheral anti-estrogenic effect of CC leads to prolonged depletion of estrogens receptors, adversely affecting endometrial growth and development as well as quantity and quality of cervical mucus. Persistent blockade of estrogen receptor leads to CC resistance and is associated with reduced ovulation and pregnancy rates. Available evidences suggest Letrozole is superior to CC owing to the lack of persistent anti-estrogenic action due to its short half- life and lack of action on estrogen receptors. This typically leads to monofollicular growth and also higher live birth rates. The current evidences suggest that Letrozole can be placed as first line therapy for the management of infertility due to PCOS and unexplained infertility.